The Role of Family Ownership in Moderating Relationship Between Related Party Transactions and Tax Avoidance - Putri Dwi Lestari; Arifin Rosid (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study examines the relationship between related party transactions (RPT) and tax avoidance in Indonesia, considering tighter RPT tax regulations and the prevalence of family-owned firms. It also explores the moderating role of family ownership using agency theory and socioemotional wealth (SEW) as the theoretical basis. The study uses four tax avoidance proxies—GAAP ETR, Current ETR, Cash ETR, and BTD—to analyze RPT in sales and purchases. Regression analysis on IDX-listed firms from 2016 to 2019 shows a positive relationship between RPT and tax avoidance (using GAAP ETR), with family ownership weakening the effect. However, sensitivity tests with alternative proxies for family ownership show the opposite result. These findings provide insights into the impact of RPT and family ownership on corporate tax behavior in Indonesia.